2019
DOI: 10.1002/cpe.5486
|View full text |Cite
|
Sign up to set email alerts
|

On‐chip evolution of combinational logic circuits using an improved genetic‐simulated annealing algorithm

Abstract: This paper presents the on-chip evolution system of combinational logic circuits by a new hybrid algorithm known as improved genetic-simulated annealing algorithm (IGASA). IGASA is based on the concept and principles of genetic algorithm (GA) and simulated annealing (SA). The main idea is to combine GA's global search ability with the advantage of SA's fast convergence to reach an optimal solution. In this paper, a new mutation operation and a repeated annealing (RA) process are introduced to overcome the prem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…All experiments were carried out using a desktop computer with a single core of i5-6500 3.2 GHz CPU. Since the performance of the algorithm can be improved by properly setting the values of parameters [38], we refer to the parameter setting methods of related literatures [32][33][34], and consider the actual requirements of the MURARP problem to set the key parameters of the HGSA algorithm. The key parameters of the HGSA algorithm are as follows:…”
Section: Experiments and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All experiments were carried out using a desktop computer with a single core of i5-6500 3.2 GHz CPU. Since the performance of the algorithm can be improved by properly setting the values of parameters [38], we refer to the parameter setting methods of related literatures [32][33][34], and consider the actual requirements of the MURARP problem to set the key parameters of the HGSA algorithm. The key parameters of the HGSA algorithm are as follows:…”
Section: Experiments and Discussionmentioning
confidence: 99%
“…According to the research of scholars, it is much more efficient to perform a local search in the area found by the GA than a direct search [31]. Therefore, it is widely adopted to combine two powerful meta-heuristics algorithms into one hybrid procedure to take advantage of their respective strengths [32][33][34]. According to the characteristics of the MURARP, we design a hybrid genetic simulated annealing (HGSA) algorithm to solve it and the flyable path of each UAV can be obtained quickly.…”
Section: Introductionmentioning
confidence: 99%
“…In response to digital trade barriers, in terms of international digital trade, Liu et al [12] conducted an empirical study on the export potential and influencing factors of digital trade in countries along the "Belt and Road Initiative" [12]. Shang et al [13] made a detailed review and exploration of the obstacles and barriers in the development of the digital service trade. The research literature found that there are many related studies on the qualitative analysis of the interpretation and evaluation of the "Belt and Road" policy and the analysis of factors affecting trade.…”
Section: Introductionmentioning
confidence: 99%
“…According to the characteristics of whether the trade inefficiency term changes with time, the stochastic frontier gravity model can be divided into two types: the timevarying and the time-invariant model [28]. Equation (13) signifies the basic form of the time-varying model.…”
mentioning
confidence: 99%
“…Li 2 investigates edge‐forwarding index of routing in the lexicographic product network, which is used to measure the congestion of an edge. Shang et al 3 presents the on‐chip evolution system of combinational logic circuits by a new hybrid algorithm known as improved genetic‐simulated annealing algorithm. Jianmin et al 4 proposes the uniform distribution code, model identification code, standard dimension code, and attribute dimensional code.…”
mentioning
confidence: 99%